Development and applications of the anaesthetists' non-technical skills behavioural marker system: protocol for a systematic review. Issue 12 (14th December 2022) - Kang, Jiamin; Hu, Jiale; Yan, Chunji; Xing, Xueyan; Tu, Shumin; Zhou, Fang
Abstract : Introduction: The high incidence of unsafe anaesthetic care leads to adverse events and increases the burden on patient safety. An important reason for unsafe anaesthesia care is the lack of non-technical skills (NTS), which are defined as personal cognitive, social or interpersonal skills, among anaesthetists. The anaesthetists' NTS (ANTS) behavioural marker system has been widely used to evaluate and improve anaesthetists' behavioural performance to ensure patient safety. This protocol describes a planned systematic review aiming to determine the validity and reliability of the ANTS behavioural marker system and its application as a tool for the training and assessment of ANTS and for improving patient safety. Methods and analysis: This systematic review follows the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocol. Studies that applied the ANTS behavioural marker system in a meaningful way, including using the ANTS behavioural marker system to guide data collection, analysis, coding, measurement, and/or reporting, which have been published in peer-reviewed journals, will be eligible. A citation search strategy will be employed. We will search Scopus and Web of Science for publications from 2002 to May 2022, which cite the three original ANTS behavioural marker system publications by Fletcher et al . We will also search the references of the relevant reviews for additional eligible studies. For each study, two authors will independently screen papers to determine eligibility and will extract the data. The quality of the included studies will be assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Checklists. A framework analysis approach that consists of five steps—familiarisation, identifying a thematic data extraction framework, indexing, charting, mapping and interpretation—will be used to synthesise and report the data. Ethics and dissemination: Ethics approval is not required for this study. The findings will be disseminated primarily through peer-reviewed publications and conference presentations. PROSPERO registration number: CRD42022297773.